2019
DOI: 10.1007/s40843-019-9437-9
|View full text |Cite|
|
Sign up to set email alerts
|

Developing near-infrared quantum-dot light-emitting diodes to mimic synaptic plasticity

Abstract: The quantum-dot light-emitting diodes (QLEDs) that emit near-infrared (NIR) light may be important optoelectronic synaptic devices for the realization of artificial neural networks with complete optoelectronic integration. To improve the performance of NIR QLEDs, we take advantage of their low-energy light emission to explore the use of poly(3-hexylthiophene) (P3HT) as the hole transport layer (HTL). P3HT has one of the highest hole mobilities among organic semiconductors and essentially does not absorb NIR li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…Zhao et al [ 124 ] subsequently reported the use of NIR QD light‐emitting diodes (QLEDs) as optoelectronic synaptic devices (Figure 8d) given the advantage of the low loss of NIR light in several technologically important materials. These NIR QLEDs had the multilayered structure of Ag/ZnO/Si NCs/PFN/P3HT /PEDOT:PSS/ITO/glass with the EL peak at the wavelength of ≈850 nm.…”
Section: Categories Of Optoelectronic Synaptic Devicesmentioning
confidence: 99%
“…Zhao et al [ 124 ] subsequently reported the use of NIR QD light‐emitting diodes (QLEDs) as optoelectronic synaptic devices (Figure 8d) given the advantage of the low loss of NIR light in several technologically important materials. These NIR QLEDs had the multilayered structure of Ag/ZnO/Si NCs/PFN/P3HT /PEDOT:PSS/ITO/glass with the EL peak at the wavelength of ≈850 nm.…”
Section: Categories Of Optoelectronic Synaptic Devicesmentioning
confidence: 99%
“…It has been envisioned that high-performance neuromorphic computing (i.e., brain-like computing) will seriously demand optoelectronically integrated artificial neural networks. For the sake of the large-scale deployment of high-performance neuromorphic computing in the future, it would be advantageous to build optoelectronically integrated artificial neural networks by using advanced silicon (Si) technologies such as Si photonics . This calls for the development of optoelectronic synaptic devices based on Si materials. …”
mentioning
confidence: 99%
“…In 2019, Pi et al [48] developed an NIR QD light-emitting diodes based on P3HT and poly[9,9-bis(3′-(N,Ndimethylamino)propyl)-2,7-flourene]-alt-2,7-(9,9-dioctylfluorene)] (PFN). The maximum UV-vis absorption peak of P3HT is at around 450nm [49] and the bandgap of P3HT utilized in this work is 2.0 eV.…”
Section: Mixed Composition Of Organic Semiconductors and Perovskite Quantum Dotsmentioning
confidence: 99%